The Effects of Personalized Nutrition Intervention In Breast Cancer Patients: A Systematic Review - Puspa Anindita Sidharta, Naomi (Riviera Publishing, 2023)
Breast cancer is a common cancer in women worldwide. Personalized nutrition interventions have gained attention as a promising approach in the treatment of breast cancer. This systematic review aimed to evaluate their effectiveness. A comprehensive search of ScienceDirect and PubMed databases was conducted from 2018 to 2023 using the keyword